Physical Medicine and Rehabilitation Management in Patients with Long COVID-19 and Thymoma-associated Myasthenia Gravis: A Case Report - Tambunan, Tresia Fransiska Ulianna; Nathania, Eugene; Putryanti, Rimnauli Deasy Putryanti; Tifany, Elisabeth Pauline; Kurnain, Dave Nicander (Respiratory Science, 2024)
Background: Myasthenia gravis is an autoimmune disease that causes muscle weakness and fatigue due to antibodies attacking the acetylcholine receptor. In patients with MG, fatigue can be worsened by concurrent long COVID, leading to further deterioration of cardiorespiratory function. Case: A 44-year-old woman with long COVID syndrome and thymoma-associated myasthenia was given an exercise program that aimed to overcome fatigue so that the patient could carry out her role as a housewife, and to prepare for thymectomy surgery. Before exercise, patients were educated to take pyridostigmine 1 hour earlier. During exercise, the patient was monitored to prevent excessive fatigue. At the end of the training session, the patient was asked to observe for signs of exacerbation until the next training session. Discussion: Pulmonary rehabilitation (PR) can be beneficial for patients with thymoma-associated MG and long COVID-19, but it requires special strategies. PR typically starts with light weights and gradually increases in intensity. It has been shown to improve fatigue and cardiorespiratory endurance, as indicated by a successful 6-minute walk test after 4 weeks of training intervention. Conclusion: Pulmonary rehabilitation plays an important role in increasing cardiorespiratory endurance and functional capacity for surgery preparation. The provision of pulmonary rehabilitation programs must be tailor-made according to the patient's functional ability and underlying disease to achieve optimal goals.